THE IMPORTANCE OF SOLFEGGIO IN CHILDREN’S MUSIC AND ART SCHOOLS (Web of Teachers: Inderscience Research, 2025)
This article provides a detailed description of the history of solfeggio, scientific analyses of this discipline by European and local scientists, and the use of various methods for effective study of solfeggio by students of music and art schools.